Strategi Komunikasi dan Resolusi Konflik Umat Beragama Melalui Pendekatan Psikologi Islam - Wikanda, Fauji; Salianto, Salianto (Universitas Medan Area, 2025)
This article aims to examine communication strategies and religious conflict resolution through an Islamic psychological approach. The paper is compiled using a library research approach. Data is collected from various literature sources, such as books, scholarly articles, journals, and previous research findings. In the historical records of humankind, social conflict is an unavoidable phenomenon that often arises from differences in perspectives ranging from thoughts and moral values to, at its most extreme, warfare. To understand how Islam views conflict resolution, it is necessary to study primary sources such as the Qur'an and Hadith, as well as interpretations by Islamic scholars concerning verses that address social conflict. In Islamic psychology, conflict resolution can be achieved through various approaches, including clarification (tabayyun), mediation (tahkim), reconciliation (islah), doing good (ihsan), mutual consultation (musyawarah), forgiveness, acting justly, and upholding freedom. Therefore, Islam as a religion of “rahmatan lil ‘alamin” carries the principle of promoting peace and harmony in the lives of all humankind.